An emulsion containing leech extract - Ahmad, Kausar; Maryanto, Maryanto; Abdul Talib, Mat Sharil (2015)
THE PRESENT INVENTION RELATES TO AN EMULSION FOR TOPICAL APPLICATION CHARACTERISED BY: 25% BY WEIGHT OF EMOLLIENT; 0.1 - 7.0% BY WEIGHT OF STABILISER; 1.0 - 25% BY WEIGHT OF EMULSIFIER; 30.0 - 50.0% BY WEIGHT OF SOLVENT; AND 1.0 - 5.0% BY WEIGHT OF LEECH EXTRACT DERIVED FROM HIRUDINARIA MANILLENSIS.